Analysis of Final Summative Assessment Test Items for Grade 6 Elementary School in Physical Education Using Anates - Deppy Widianto; Wanda Nugroho Yanuarto; Subuh Anggoro (UM Purwokerto Press, 2025)
This study evaluated the quality of test items in the Physical Education, Sports, and Health (PJOK) Final Summative Assessment (ASAT) for Grade 6 students at SDN Kutasari 03 Cipari, Cilacap Regency. Using ANATES software, 25 multiple-choice and 10 essay questions were analyzed from a sample of 5 students. The analysis focused on reliability, discriminating power, difficulty level, and distractor effectiveness. Results revealed high reliability for multiple-choice questions (0.72) and very high reliability for essay questions (0.93). For multiple-choice items, 48% demonstrated good discriminating power, 32% had balanced difficulty levels, and 40% showed significant correlations with total scores. Among essay questions, 60% exhibited good discriminating power, and all items had moderate difficulty levels. Based on these findings, several test items require revision to enhance assessment quality in the Physical Education subject, particularly focusing on improving discriminating power and difficulty balance for optimal student evaluation.